PENINGKATAN KESEJAHTERAAN MASYARAKAT TANI MELALUI PELATIHAN DAN PENDAMPINGAN ABON CABAI DI DUSUN TANGGUNG MULYO KEDIRI - Selah Nurul Ma'rifah; IVA MALA; Sokhifatussaniyah; Sutantri (Institut Agama Islam Tribakti Kediri, 2022)
The volatility of chili prices is a protracted problem that has not been completely resolved. Meanwhile, the majority of Dusun Responsibility Mulyo people are chili farmers whose livelihoods are supported by the sale of chili products. Therefore, this service is carried out with the aim of maintaining the stability of chili farmers' income which has an impact on the welfare of the Dusun Responsibility Mulyo community and stimulates the potential of MSMEs in the village. The method used is PAR and a case study approach with participatory observation. The solution that can be used is to conduct training and provide assistance in processing chili products into semi-finished processed materials, namely “Abon Cabai”